Investigation of Shariah Compliant Green Firm Performance Using Eco-Efficient Infrastructure and Green Organizational Capabilities: - Kashif, Uzma (Islamic Banking and Finance Review, 2023)
The primary goal of this study is to investigate the impact of eco-efficient infrastructure and organizational capabilities on shariah compliant shariah compliant green organizational performance, with shariah compliant sustainable production serving as a moderator. To achieve the study’s goal, data were collected from 528 respondents in the manufacturing sector using a stratified sampling technique. The findings showed that a firm’s eco-efficient infrastructure and organizational capabilities play an important role in achieving green performance; additionally, Shariah-Compliant Sustainable Production plays an important mediating role. This study contributes to the development of policies for organizations to improve their green performance and theoretically eco-efficient infrastructure, which has been overlooked in previous literature.